SPIRITUALITY, SPIRITUAL COPING AND MENTAL WELL-BEING AMONG MALAYSIAN MEDICAL AND HEALTH SCIENCES STUDENTS - Nur Faqihah Amni Mazzuki; Nik Syazwani Sukeri; Mohd Ibrahim Abdullah; Usman Jaffer; Nursyuhaidah Mohd Kadri; Che Mohd Nasril Che Mohd Nassir, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study aims to examines the relationship between mental health, spirituality, and spiritual coping among medical and health sciences university students in East Coast Peninsular Malaysia. Using the Depression, Anxiety, and Stress Scale (DASS-21), data were collected from 484 students predominantly in various medical and health sciences disciplines. The study explored how spirituality, measured by the Spirituality Scale (SS) and the Spiritual Coping Questionnaire (SCQ), influences depression, anxiety, and stress levels. Findings revealed that higher spirituality was significantly associated with lower depression, anxiety, and stress. Positive spiritual coping was linked to lower depression, while negative spiritual coping was associated with higher levels of depression, anxiety, and stress. These results indicate that spirituality can act as both a protective factor and a source of distress, depending on the coping mechanisms employed. The study underscores the necessity of culturally sensitive mental health interventions that incorporate spiritual dimensions, providing a holistic approach to support students' psychological well-being. This research contributes valuable insights for educators, mental health professionals, and policymakers, highlighting the complex interplay between spirituality and mental health in a multicultural context.